Diagnostic Accuracy of Magnetic Resonance Imaging Compared with Arthroscopy in Knee Injuries Among Paramilitary Personnel at a Tertiary Care Center - Thapa, Rossu; Lamichhane, Suman; Bhusal, Amrit; Shrestha, Sailendra Kumar Duwal; Yadav, Sumit; Swar, Avishek; Joshi, Ram Datt (Nepal Journal of Medical Sciences, 2026)
Introduction: Accurate diagnosis of intra-articular knee injuries is essential to guide management and prevent long-term complications. Arthroscopy is the diagnostic gold standard but is invasive, whereas Magnetic Resonance Imaging (MRI) offers a non-invasive alternative. The objective of this study is to assess the diagnostic accuracy of MRI in detecting ligamentous, meniscal, and chondral injuries of the knee by correlating findings with arthroscopy.Methods: Paramilitary personnel with clinically suspected knee injuries who underwent both MRI and arthroscopy were included. MRI findings were compared with arthroscopy, the reference standard, and diagnostic performance indices were calculated.Results: MRI demonstrated high sensitivity and specificity for anterior cruciate ligament, posterior cruciate ligament, and meniscal tears, with relatively lower accuracy for chondral injuries.Conclusions: MRI is a reliable, non-invasive tool for diagnosing major intra-articular knee injuries. Correlation with arthroscopy highlights its strengths and limitations, supporting its role in preoperative evaluation and surgical planning.